Design and implementation of an embedded web server based on ARM - Mo Guan; Minghai Gu (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
In this paper, the embedded web server, which take Samsung corporation's ARM9-S3C2440AL processor as core, is designed, it's operating system is Linux, the system hardware architecture is presented. Then the process of the Linux operating system being transplated on ARM is introduced. The realization of Boa and dynamic interaction between browser and the embedded system by using CGI are especially analyzed. Finally the implemented embedded web server is tested to indicate that it responding rapidly and operates efficiently and steadily, which achieves the expectant designing purpose.